Vprašanje zaupnosti informacij med delavskimi predstavniki v nadzornem svetu ter svetom delavcev - Franca, Valentina (Delavci in delodajalci, 2018)
The article analyses legal matters that appear in relationships between employees' representatives in the supervisory board and the works council as the body that appoints or elects such employees' representatives. Communication of information, which is marked as a trade secret but which directly relates to the position of employees in the company, is a particularly pressing issue. When determining if a specific piece of information is a trade secret, the interest of employees and fundamental principles of employee participation must be taken into account, in addition to corporate rules and the company's interest.
Keywords: confidentiality of information; delavski predstavniki v nadzornem svetu; employees' representatives in the supervisory board; nadzorni svet; poslovna skrivnost; supervisory board; svet delavcev; trade secret; works council; zaupnost informacij